Delayed Methotrexate Clearance Despite Carboxypeptidase-G2 (Glucarpidase) Administration in 2 Patients With Toxic Methotrexate Levels. Issue 2 (March 2018) - Wyatt, Kirk D.; Cooper, Jeffrey; Scott, Katherine; Broomall, Eileen; Altaf, Sadaf; Hogan, Marie C.; Rodriguez, Vilmarie; Khan, Shakila
Abstract : High-dose methotrexate has been a treatment for osteosarcoma; however, its nephrotoxic effects are considerable. Carboxypeptidase-G2 (glucarpidase) was approved by the US Food and Drug Administration in 2012 for treatment of toxic methotrexate levels. We report our experience using glucarpidase under compassionate use before Food and Drug Administration approval in 2 patients who had delayed methotrexate clearance and prolonged kidney injury despite glucarpidase administration. Our results show that patients with methotrexate toxicity may require repeated doses of glucarpidase in addition to supportive measures, such as dialysis.